MORPHOLOGICAL CHARACTERISTICS AND TOTAL FLAVONOID CONTENT IN PEEL EXTRACTS OF FOUR BANANA CULTIVARS FROM INDONESIA (Musa spp.) - Hida Arliani; Supriyadi Supriyadi; Rina Sri Kasiamdari; Budi S. Daryono (SEAMEO BIOTROP, 2025)
HIGHLIGHTS- Wild banana morphology links to high peel flavonoid content.- Klutuk banana peel has the highest antioxidant potential.- Morphological traits can predict nutraceutical value in bananas.- Banana peel waste is a valuable source of natural antioxidants.- Conservation of wild germplasm is crucial for bioactive compounds.ABSTRACTBanana is a commodity with high genetic diversity in Indonesia, often leading to identification issues due to synonymy and homonymy. Accurate morphological characterization is essential for germplasm management and breeding programs. Concurrently, high consumption of banana generates significant banana peel waste, which is a potential source of bioactive compounds like flavonoids. This study aimed to characterize the morphology of four banana varieties (Cavendish, Kepok, Raja, Klutuk) from the Yogyakarta Banana Germplasm Garden and analyze the total flavonoid content (TFC) in banana peels. Morphological characterization was conducted following the IPGRI descriptor list, and TFC was measured spectrophotometrically and expressed as mg Quercetin Equivalent per gram (mgQE/g). The results revealed distinct morphological profiles for each variety, with the wild-type Klutuk banana exhibiting the tallest pseudostem and seedy fruit. The TFC analysis showed a significant variation, where Klutuk peel had the highest content (0.453 mg QE/g), followed by Kepok (0.386 mg QE/g), Cavendish (0.146 mg QE/g), and Raja (0.139 mg QE/g). The high flavonoid content in the morphologically distinct Klutuk variety suggests a correlation between its wild morphological traits and enhanced production of defensive phytochemicals. These findings underscore the value of morphological data for identifying cultivars with high nutraceutical potential, promoting the utilization of banana peel waste as a source of natural antioxidants.